Network analysis and traceability on ethereum blockchain - Su, Voon Hou (Nanyang Technological University, 2021)
The rise in popularity of blockchain technology has led to the development of many interesting cryptocurrencies with different functionalities. One such blockchain technology is Ethereum, a decentralized, open source blockchain featuring smart contract functionality with Ether as its native cryptocurrency. Ethereum introduces a novel ecosystem of human users and autonomous agents in the form of smart contracts. As the most actively used blockchain and second largest cryptocurrency by market capitalization, the blockchain contains a vast amount of information documenting the interactions between user-to-user, user-to-contract, contract-to-user and contract-to-contract, all of which can be represented in a network. To analyse these interactions in the form of networks, the required data has to be extracted from the blockchain, transformed, and loaded into the desired format and/or software of choice for analysis. As the data is large, it is difficult to manage and ETL the data. We have come up with a tool named EtherNet that aims to facilitate the process of performing ETL tasks from a single source of truth, namely BigQuery, into its graph equivalent representations for network analysis.